Process Versus Outcome Thought Focus and Advertising - Escalas, Jennifer Edson; Luce, Mary Frances (Journal of Consumer Psychology, 2003)
Recent social psychological research demonstrates that certain types of mental simulation are particularly useful for helping individuals reach the future they envision (e.g., Taylor, Pham, Rivkin, & Armor, 1998). More specifically, Taylor's (Pham, Taylor, 1999; Taylor et al., 1998) recent research indicates that the most successful simulations focus on the process of reaching a goal rather than on the outcomes or attainment of the goal. In this article, we extend consideration of process‐ versus outcome‐focused thought to advertising. In studies manipulating the focus of participants’ thoughts while viewing a print advertisement, we find that process‐focused thought results in significantly higher behavioral intentions than outcome‐focused thought when advertisement arguments are strong. However, in the case of weak advertisement arguments, process‐focused thought actually lowers behavioral intentions compared to thoughts focusing on the end result or outcome of product usage. Thus, in addition to increasing the persuasive power of strong advertising claims, process‐focused thinking appears to make individuals better or more discerning consumers who do not form behavioral intentions when it is inappropriate to do so.